Overview of the Main Directions of Budgetary Policy and Innovations of the Russian Budgetary Legislation for the Period of 2016-2018 - Kolupaev, Roman Vladimirovich; Rogacheva, Lubov' Ivanovna; Ul'rikh, Irina Vladimirovna; Novikov, Roman Anatolyevich; Rogachev, Maxim Alexandrovich (International Journal of Economics and Financial Issues, 2016)
This article reviews the main directions and innovations of budgetary policy and budgetary legislation of the Russian Federation for the period of 2016-2018. Measures to be taken to increase the effectiveness of budget expenditures and refine the budgetary system, develop and implement the tax policy have been proposed. Such issues as state regulation of financial markets, insurance and auditing activities, implementation of a single financial, credit and monetary policy, management of the public debt and financial assets of the Russian Federation have also been reviewed. A comparative analysis of the conjunctural conditions of formation of the budgetary policy in the pre- and post-sanctions period has been conducted. Keywords: budget, crisis, anti-crisis measures, inflation, the dollar exchange rate. JEL Classifications: H61, H21, K23